Dexmedetomidine as Neuroanesthesia Management in Patient with Meningioma Craniotomy - Kumoro, Mohammad Aji; Prihatno, MM Rudi; Kartinofan, Aditya Pradana (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Meningiomas are the type of tumour that grows from the protective membranes of the brain, which line both the brain and spinal cord. The incidence rate of meningioma between females and males is 2:1 and tt is a fairly common neurosurgical case at Margono Soekarjo General Hospital Purwokerto. Dexmedetomidine is the drug of choice used for sedation and analgesia. In various literature, it is said that the use of dexmedetomidine will reduce hemodynamic fluctuations during surgery. A 49-year-old man was hospitalized because of cephalgia and hemiparesis of his left extremity. Computed tomography scan revealed a solid tumour at parietooccipitalis region, lobulated, measuring 7,2 x 7,1 x 4,4 cm, and an increase in intracranial pressure. General anesthesia was administered, beginning with premedication using sufentanil for analgesia, followed by induction with thiopental, and rocuronium for muscle relaxation to facilitate intubation. Dexmedetomidine is an attractive option available for anesthesiologist for maintaining general anesthesia. In this surgical procedure to remove an intracranial tumor, appropriate induction and monitoring of the patient's condition during surgery is required to prevent the risk of increasing intracranial pressure. Dexmedetomidine reduces cerebral blood flow, decreases intracranial pressure, reduces the rate of cerebral oxygen metabolism, and maintains cerebral perfusion pressure. Good management of neuroanesthesia supports the maintenance of hemodynamic stability and leads to better outcomes in craniotomy surgery. Dexmedetomidine has benefits on maintenance of anaesthesia in neurosurgical procedures.